(Q, S, R)-Dissipativity Analysis of Large-Scale Networked Singular Systems With Time Delays - Lingze Zhang; Huabo Liu (IEEE Access)
This paper investigates the strictly (Q, S, R)-dissipative issues of large-scale networked singular time-delay systems composed of multiple subsystems in discrete time. These subsystems are interconnected arbitrarily and possess distinct dynamic characteristics. The existing lumped analysis methods encounter significant computational challenges when dealing with such systems. By fully leveraging the system structure, sufficient conditions for the strict dissipativity are derived. Building upon this foundation, a sufficient condition is provided further that depends solely on the parameters of the individual subsystem, greatly enhancing computational efficiency. Through numerical simulations and a case study, the derived conditions demonstrate effectiveness and superiority in analyzing the strict dissipativity of large-scale networked singular time-delay systems.